Specific Targeting of Lymphoma Cells Using Semisynthetic Anti-Idiotype Shark Antibodies - Macarrón Palacios, Arturo; Grzeschik, Julius; Deweid, Lukas; Krah, Simon; Zielonka, Stefan; Rösner, Thies; Peipp, Matthias; Valerius, Thomas; Kolmar, Harald (Frontiers in Immunology, 2020)
The B-cell receptor (BCR) is a key player of the adaptive immune system. It is a unique part of immunoglobulin (Ig) molecules expressed on the surface of B cells. In case of many B-cell lymphomas, the tumor cells express a tumor-specific and functionally active BCR, also known as idiotype. Utilizing the idiotype as target for lymphoma therapy has emerged to be demanding since the idiotype differs from patient to patient. Previous studies have shown that shark-derived antibody domains (vNARs) isolated from a semi-synthetic CDR3-randomized library allow for the rapid generation of anti-idiotype binders. In this study, we evaluated the potential of generating patient-specific binders against the idiotype of lymphomas. To this end, the BCRs of three different lymphoma cell lines SUP-B8, Daudi, and IM-9 were identified, followed by reformatting the variable domains and expression of the resulting monoclonal antibodies. The SUP-B8 BCR served as antigen in fluorescence-activated cell sorting (FACS)-based screening of the yeast-displayed vNAR libraries which resulted after three rounds of screening in the enrichment of antigen-binding vNARs. Five vNARs were expressed as Fc fusion proteins and consequently analyzed for their binding to soluble antigen using biolayer interferometry (BLI) revealing binding constants in the lower single-digit nanomolar range. These variants showed specific binding to the parental SUP-B8 cell line confirming a similar folding of the recombinantly expressed proteins compared with the native cell surface-presented BCR. First initial experiments to utilize the generated vNAR-Fc variants for BCR-clustering to induce apoptosis or ADCC/ADCP did not result in a significant decrease of cell viability. Here, we report an alternative approach for a personalized B-cell lymphoma therapy based on the construction of vNAR-Fc antibody-drug conjugates to enable specific killing of malignant B cells, which may widen the therapeutic window for B-cell lymphoma therapy.